2021
DOI: 10.18685/ejmr(8)1_ejmr-21-010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis associated with COVID-19 (U07.1), Pneumonia- Unspecified (J18.9) and other types of admissions: A restricted medical scheme case study- South Africa

Abstract: The primary objective of this study was to assess the characteristics of patients admitted for COVID-19, ‘J18.9 Pneumonia, unspecified organism’ and other types of diagnoses. The aim was to assess as to what extent do COVID-19 related admissions changed to pneumonia, and as to what extent do ‘J18.9 Pneumonia, unspecified organism’ related admissions that changed to COVID-19 diagnosis at discharge stage. The secondary objective of the study was to assess’ predictors of readmissions in private hospitals. The rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Willie and Motsepe found that COVID-19 ICU inpatients stayed longer than 'J18.9 Pneumonia, unspecified organism' diagnosis, with median inpatient days of 13 and 6 days, respectively. A similar phenomenon was also observed in high care admissions, where the median inpatient days was 9 days vs. 7 days, respectively [1]. A study by Guo, et al analysed clinical characteristics and predicted mortality risk among patients with viral pneumonia.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Willie and Motsepe found that COVID-19 ICU inpatients stayed longer than 'J18.9 Pneumonia, unspecified organism' diagnosis, with median inpatient days of 13 and 6 days, respectively. A similar phenomenon was also observed in high care admissions, where the median inpatient days was 9 days vs. 7 days, respectively [1]. A study by Guo, et al analysed clinical characteristics and predicted mortality risk among patients with viral pneumonia.…”
Section: Discussionmentioning
confidence: 55%
“…In a prospective study by Wong, et al for patients in ICU, the most common reasons for admission were neuromuscular weakness, pneumonia, multiple traumas, and septic shock, in that order [23]. A study by Willie and Motsepe investigated diagnoses associated with COVID-19 (U07.1), Pneumonia unspecified (J18.9) and other types of admissions, on a restricted medical scheme case study in South Africa [1]. The study found that patients admitted for COVID-19 were chiefly admitted in the "other" type of admitting categories, compared to those admitted in the general ward, high care, and ICU [1].…”
Section: Admitting Facilitiesmentioning
confidence: 99%
See 3 more Smart Citations